BENTUK PROBLEM RUMAH TANGGA TERHADAP PENYIMPANGAN TINGKAH LAKU SISWA - Ahmad Fathoni; Suraji (Institut Agma Islam Hamzanwadi NW Lombok TImur, 2020)
The objectives of this study are: (1) to know the form of household problems and the form of deviant behavior experienced by students, (2) how are the efforts of the teacher in dealing with students behaving deviantly because of their household problems. The research method used is qualitative with a case study form. There are some household problems experienced by student, that are: broken home (divorce) and parents' busy work. While the forms of deviant behavior of student who have household problems are divided into two types, namely: individual deviant behavior and primary deviant behavior. The obstacles experienced by teacher in responding to deviations in the behavior of students who have household problems include: (1) teacher communication with students having household problems, and (2) teacher communication with parents of students.